A distributed geospatial approach to describe community characteristics for multisite studies. Issue 1 (5th February 2021) - Ryan, Patrick H.; Brokamp, Cole; Blossom, Jeff; Lothrop, Nathan; Miller, Rachel L.; Beamer, Paloma I.; Visness, Cynthia M.; Zanobetti, Antonella; Andrews, Howard; Bacharier, Leonard B.; Hartert, Tina; Johnson, Christine C.; et al.
Abstract: Understanding place-based contributors to health requires geographically and culturally diverse study populations, but sharing location data is a significant challenge to multisite studies. Here, we describe a standardized and reproducible method to perform geospatial analyses for multisite studies. Using census tract-level information, we created software for geocoding and geospatial data linkage that was distributed to a consortium of birth cohorts located throughout the USA. Individual sites performed geospatial linkages and returned tract-level information for 8810 children to a central site for analyses. Our generalizable approach demonstrates the feasibility of geospatial analyses across study sites to promote collaborative translational research.